2017
DOI: 10.1101/143768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precentral gyrus abnormal connectivity in male and female schizophrenia patients

Abstract: The present study demonstrates the Precentral gyrus (PreCG) alteration and its abnormal connectivities in Schizophrenia (SCH) patients. The resting-sate functional magnetic resonance imaging (rs-fMRI) data of healthy control subjects and SCH patients (Centre for Biomedical Research Excellence data set) are used to examine the aberrant functional brain connectome in SCH which contains raw anatomical and functional MR data from 72 patients with Schizophrenia and 75 healthy controls, ranging in age from 18 to 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Future studies with drug-naïve patients and studies within the ketamine model of schizophrenia could involve modulation by dopaminergic substances. The increase of theta-band connectivity in this study involved a distinct network comprising areas relevant for auditory processing ( 73 ), motor-function ( 74 ), representations of the self ( 75 ), areas relevant to language processing ( 76 ) and thought disorders ( 77 ), all of them highly relevant for schizophrenia.…”
Section: Discussionmentioning
confidence: 77%
“…Future studies with drug-naïve patients and studies within the ketamine model of schizophrenia could involve modulation by dopaminergic substances. The increase of theta-band connectivity in this study involved a distinct network comprising areas relevant for auditory processing ( 73 ), motor-function ( 74 ), representations of the self ( 75 ), areas relevant to language processing ( 76 ) and thought disorders ( 77 ), all of them highly relevant for schizophrenia.…”
Section: Discussionmentioning
confidence: 77%
“…They are Precentral gyrus, Hippocampus Caudate nucleus, Thalamus, Superior temporal gyrus and Lenticular nucleus. Specifically, recent studies have shown dysfunction of the precentral gyrus has long been thought to play a role in the impairments of voluntary movement associated with Schizophrenia and it has significantly reduced functional activity in patients with schizophrenia [39]- [41]. Hippocampus is currently recognized as a brain region associated with schizophrenia, and its reduced volume can cause patients to experience rest, hearing and memory dysfunction [42], [43].…”
Section: E Qualitative Analysis Of Experimental Resultsmentioning
confidence: 99%